Infant mortality in the municipality of São Paulo: trend and social inequality (2006-2019) - Katia Cristina Bassichetto; Margarida Maria de Azevedo Tenório Lira; Edige Felipe de Sousa Santos; Ivan Arroyave; Samantha Hasegawa Farias; Marilisa Berti de Azevedo Barros (Universidade de São Paulo, 2023)
ABSTRACT OBJECTIVE Considering the published evidence on the impact of recent economic crises and the implementation of fiscal austerity policies in Brazil on various health indicators, this study aims to analyze how the trend and socio-spatial inequality of infant mortality behaved in the municipality of São Paulo from 2006 to 2019. METHODS This is an ecological study with a temporal trend analysis that was developed in municipality of São Paulo, using three residence area strata differentiated according to their social vulnerability following the 2010 São Paulo Social Vulnerability Index. Infant mortality rate, as well as neonatal, and post-neonatal mortality rates, were calculated for each social vulnerability stratum, each year in the period, and for the first and last three triennia. Temporal trends were analyzed by the Prais-Winsten regression model and inequality magnitude, by rate ratios. RESULTS We found a decline in infant mortality rate and its components from 2006 to 2015, greater in the stratum with low social vulnerability and in the post-neonatal period when compared to the neonatal one. This decline ended in 2015, stagnating in the next period (2016-2019). Our analysis of infant mortality inequality across social vulnerability stratum showed a significant increase from the initial to the final triennia in the analyzed period; rate ratios increased from 1.36 to 1.48 in the high stratum (compared to the low social vulnerability stratum), and from 1.19 to 1.32 between the medium and low social vulnerability strata. CONCLUSIONS The observed stagnation of infant mortality rate decline in 2015 and the increase in socio-spatial inequality point to the urgent need to reformulate current public policies to reverse this situation and reduce inequalities in the risk of infant death.